(untitled) (Learning to Teach Language Arts, Mathematics, Science, and Social Studies Through Research and Practice, 2023)
Children learn naturally through exploring their environment. There are many academic benefits for young children in a play-based classroom. The benefit of play supports children’s development in five domains: physical, language, social, emotional, and cognitive. Teachers can support a deeper level of learning by implementing a play-based learning classroom. A teacher’s perspectives and roles have a significant impact on their student’s learning. There are many innovative types of play that can be implemented in the classroom. When children can make choices in their learning it will indirectly increase their cognitive academic skills. Play is holistic and supports the whole child and their individual needs. Keywords: play-based pedagogy, developmental domains, implementation and facilitating play, teachers’ perspectives and roles, theorists